Do algorithms dream of mistaken contracts? Supreme Court case summary: Quoine Pte Ltd v B2C2 Ltd - HAKIM, Lokman Bin Mohamed Rafi (Institutional Knowledge at Singapore Management University, 2021)
Can an agreement which is formed purely through the operation of algorithms be considered a binding contract? If so, can such a contract be unilaterally cancelled because of a mistake, where such mistake resulted in trades being concluded at 250 times the market rate? This was the question before the Court of Appeal (“CA”) in the case of Quoine Pte Ltd v B2C2 Ltd [2020] SGCA(I) 2.